Networks underlying paroxysmal fast activity and slow spike and wave in Lennox-Gastaut syndrome - Pillay, Neelan (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: To use EEG-fMRI to determine which structures are critically involved in the generation of paroxysmal fast activity (PFA) and slow spike and wave (SSW) (1.5–2.5 Hz), the characteristic interictal discharges of Lennox-Gastaut syndrome (LGS). METHODS: We studied 13 well-characterized patients with LGS using structural imaging and EEG-fMRI at 3 tesla. Ten patients had cortical structural abnormalities. PFA and SSW were considered as separate events in the fMRI analysis. RESULTS: Simultaneous with fMRI, PFA was recorded in 6 patients and SSW in 9 (in 2, both were recorded). PFA events showed almost uniform increases in blood oxygen level–dependent (BOLD) signal in “association” cortical areas, as well as brainstem, basal ganglia, and thalamus. SSW showed a different pattern of BOLD signal change with many areas of decreased BOLD signal, mostly in primary cortical areas. Two patients with prior callosotomy had lateralized as well as generalized PFA. The lateralized PFA was associated with a hemispheric version of the PFA pattern we report here. CONCLUSION: PFA is associated with activity in a diffuse network that includes association cortices as well as an unusual pattern of simultaneous activation of subcortical structures (brainstem, thalamus, and basal ganglia). By comparison, the SSW pattern is quite different, with cortical and subcortical activations and deactivations. Regardless of etiology, it appears that 2 key, but distinct, patterns of diffuse brain network involvement contribute to the defining electrophysiologic features of LGS.